THE APPLICATION OF COOPERATIVE LEARNING: JIGSAW II TECHNIQUE IN IMPROVING STUDENTS’ READING COMPREHENSION OF EXPOSITORY TEXT - Nurwanti, Nurwanti; Asrifan, Andi; Haedar, Haedar (Study Program of English Literature, 2019)
The research was conducted to find out whether or not the use of Jigsaw II technique improves the reading comprehension significantly better than the use of the conventional method of the eleventh grade students of SMA Negeri 8 Takalar, it covered students’ literal comprehension, inferential comprehension and critical comprehension of expository text and whether or not the students are interested in the use of Jigsaw II technique in learning reading of expository text. This research method employed was quasi-experiment. The research data were obtained through the test and questionnaire which were analyzed by SPSS 17.0 program. Data of test were analyzed using T-test to know students’ reading comprehension in terms of literal, inferential, and critical of expository text. Data of the questionnaire were analyzed by using descriptive statistics to see the students’ interest in joining the reading class of expository text through Jigsaw II technique. The research findings indicated that (1) Jigsaw II technique gave a higher contribution to the students’ reading comprehension of expository text. The mean score of pretest of the experimental and control group was significantly different after treatment by using Jigsaw II technique. The mean score of posttest of the experimental group was higher than the control group (84.16 > 62.91). Thus, the use of Jigsaw II technique was effective. Besides, all the three levels of comprehension improved after doing treatment; the literal comprehension got the highest improvement was 92.19>76.69. It was followed by inferential comprehension which got 83.75>66.25, and critical comprehension which got76.56 > 42.81.